Sustainable Silica‐Carbon Nanofiber Hybrid Composite Anodes for Lithium‐Ion Batteries - Anne Beaucamp; Amaia Moreno Calvo; Deaglán Bowman; Clotilde Techouyeres; David Mc Nulty; Erlantz Lizundia; Maurice N. Collins (Macromolecular Materials and Engineering)
Abstract Alternative anode materials with increased theoretical specific capacities are under scrutinity as a replacement to graphite in lithium‐ion batteries (LiBs). Silicon oxides offer increased capacities compared to graphite and do not suffer the same level of material expansion as pure Si. Consequently, they are an intermediate commercial anode material, on the pathway toward pure Si anodes. In this study, stable Silica/carbon (SiO2/C) nanofibers are successfully developed from tetraethyl orthosilicate (TEOS) using poly(vinylpyrrolidone) (PVP). The fibers show excellent stability after calcination, with silica evenly dispersed within the fibers exhibiting a surface area of 327 m2 g−1. This study demonstrates that the electrochemical performance of SiO2/C composite anodes is significantly influenced by the silica content. SiO2/C composites with ≈68 at% SiO2 achieve reversible capacities of 315.6 and 300.9 mAh g−1, after the 2nd, and 800th cycles, respectively, at a specific current of 100 mA g−1, with a remarkable capacity retention of 95.3%. In a second stage, lignin is added as a potential nanostructuring agent. The addition of lignin to the sample reduces the amount of silica without significantly impacting its performance and stability. Tailoring the composition of SiO2/C composite anodes enables stable capacity retention over the course of hundreds of cycles.